SOLUCIÓN COMO FUNCIÓN LINEAL APROXIMADA EN UN REDUCIDO INTERVALO DE ECUACIONES DIFERENCIALES DE PRIMER ORDEN CON FUNDAMENTO EN EL PROBLEMA DE CAUCHY - CARLOS MANUEL MATA RODRIGUEZ (Revista Ingeniería, Matemáticas y Ciencias de la Información)
The approximation is, as we all know, an inexact form that it is sufficiently logical to be use-ful. In technologicalcalculations, the approximation plays a fundamental role in the moment of showing the results, because the exact valuesare difficultly obtained. In mathematics, the approximation is specifically applied to numeric calculations, and, in moresophisticated forms, to such objects like mathematical functions. The adjustment of curves is included in this analysis asa problem of approximation. A very well-known case is the one of the method of the minimum squares, in which issearched a straight line that adjust perfectly to a series of previously calculated points. And it is, in fact, on mathematicalfunctions, especially on the lineal function, that it will be used in this article, as expression of calculation, to obtain anapproximate sufficiently exact in the solution of differential equations in the form dy/dx = f(x,y) that cannot be resolvedby the classic methods.